Balancing a wheeled inverted pendulum with a single accelerometer in the presence of time delay. (March 2017) - Xu, Qi; Stepan, Gabor; Wang, Zaihua
The output of an accelerometer often has coupled components of displacement and acceleration, and is rarely used individually for balancing tasks. In order to balance a wheeled inverted pendulum like the Segway, the conventional control usually requires gyroscopes or a combination of accelerometers and gyroscopes. In this paper, we prove that even in the presence of time delay, a wheeled inverted pendulum can be well stabilized with only one accelerometer as the sensor when the mechanical structure is slightly modified. The key idea is the introduction of an additional damper that does not have a physical connection with the wheels. Moreover, we show that balancing can be achieved with an appropriately selected accelerometer position over a range of time delays.